(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Streptomyces sp. has been known to produce antibiotics and other bioactive natural products. However, the production of these secondary metabolites depends on the culture conditions, where in most cases the secondary-metabolite genes are not expressed in fermentation culture. Recently, a novel fermentation method known as combined-culture has been introduced to unlock these â€œsilentâ€ genes, hence induces the production of cryptic metabolites. We report herein, our preliminary work on combined-culture using two soil-borne bacterial strains; Streptomyces and Tsukamurella. From the results, it is shown that the presence of Tsukamurella, a mycolic acid-containing bacterium induces the production of new metabolites in Streptomyces. Moreover, the production of compounds associated with Streptomyces was enhanced via combination-culture as compared to culture of Streptomyces strain alone. These findings may promote the feasibility of combined-culture in unlocking the â€œsilentâ€ genes of microorganisms which could lead to the discovery of novel metabolites.